DEVELOPMENT OF PASTA TORTUT (TORTELLINI JEWAWUT) WITH PADANG SAUS FROM JEWAWUT FLOUR - Titin Hera Widi Handayani, Devi Carissa (Prosiding Pendidikan Teknik Boga Busana, 2020)
Indonesia has a variety of types of cereal but, its use has not been carried out maximally, one of which is jewawut which has antioxidant content, calcium and protein up to 13%, more than rice which is only about 8% to 10%. Pasta is a dish made from a mixture of flour, water, eggs, and salt that forms a mixture that can be formed into a variety of sizes and shapes. Pasta is an alternative product to increase the use of jewawut. This study uses the type of R & D research, with the 4D method (define, design, development, disseminate). The purpose of this study is to find the right recipe, to find out the level of consumer acceptance and to find out the nutritional content in Tortut Pasta with Padang Sauce. The results of the study state that the recipe received by consumers is by comparison of jewawut flour and wheat flour by 40%: 60% with a level of acceptance of 3.7 (accepted) with a water content of 50.94%, fat 3.41%, ash 8.18%, Protein 10.06%, crude fiber 0.97% and carbohydrates 27.40%. Keywords: Jewawut Flour, Padang sauce, Tortellini Pasta